How do you evaluate the function when x = -3, 0, and 2 for g(x) = -9x + 1?

1 Answer
Jul 2, 2017

See a solution process below:

Explanation:

To evaluate the function you need to replace the value of x for x in the function g(x).

1) x = -3; substitute color(red)(-3) for color(red)(x) in g(x):

g(color(red)(x)) = -9color(red)(x) + 1 becomes:

g(color(red)(-3)) = (-9 * color(red)(-3)) + 1

g(color(red)(-3)) = 27 + 1

g(color(red)(-3)) = 28

2) x = 0; substitute color(red)(0) for color(red)(x) in g(x):

g(color(red)(x)) = -9color(red)(x) + 1 becomes:

g(color(red)(0)) = (-9 * color(red)(0)) + 1

g(color(red)(0)) = 0 + 1

g(color(red)(0)) = 1

2) x = 2; substitute color(red)(2) for color(red)(x) in g(x):

Try this one and see if the previous two examples showed you how to evaluate the function. Good luck!